A Review of the Studies on the Effect of Different Additives on the Fatigue Behavior of Asphalt Mixtures - Mahmoud Ameri; Mehdi Ebrahimzadeh Shiraz (Advances in Civil Engineering)
The fatigue phenomenon significantly weakens road pavement due to repeated reloading. To enhance fatigue resistance, numerous studies have explored various additives in asphalt mixtures. This review focuses on key variables influencing the effectiveness of additives, including fibers, polymers, nanomaterials, waste materials, and biomaterials, in improving the fatigue performance of asphalt mixtures. The study initially identifies different additives and fatigue testing methods used for asphalt mixtures. It evaluates the impact of factors such as modifier content and size, base asphalt binder type, mixing processes, dispersion behavior, and testing conditions on the fatigue behavior of modified asphalt mixtures. The cost-effectiveness and environmental impact of additive application have also been assessed. Additionally, research gaps and future prospects for modified asphalt mixes are outlined. Existing studies demonstrate the benefits of additives like basalt fiber, polyester fiber, styrene–butadiene–styrene (SBS), nanosilica, crumb rubber, and biooils in enhancing the fatigue life of pavement constructions. However, challenges exist in the application of modifiers due to limited practical implications and insufficient knowledge. Further research is needed on factors such as additives’ dispersity, compatibility, aging resistance, economic viability, and modifying mechanisms in morphological and micromechanical aspects to enhance the fatigue performance of the modified asphalt mixture.